HALAL ENTREPRENEURSHIP IN UZBEKISTAN: GLOBAL PRACTICE AND NATIONAL PERSPECTIVE - Ismanov Ibrohim Nabievich; Yormatov Ilmidin Toshmatovich (Web of Journals Publishing, 2024)
This article is devoted to the introduction and development of halal business practices in Uzbekistan. It analyzed international experience in the field of halal finance, investments and insurance, and considered promising directions for Uzbekistan. In particular, such issues as the development of halal financial institutions, the formation of the halal consumer goods and services market, the support of halal entrepreneurship, and the formation of halal business culture were covered.
Keywords: Halal business, Islamic finance, Islamic banking, Halal insurance, Halal products, Halal services, Halal business culture, social responsibility.